PERAN GURU PENDIDIK KHUSUS DALAM IMPLEMENTASIPROGRAM KEBUTUHAN KHUSUS BAGI PESERTA DIDIK BERKEBUTUHAN KHUSUSDI SD - Firdaus, Yayuk (Jurnal Pendidikan Khusus, 2016)
ABSTRACTSpecial educator teacher was the one who gave assistance and service toward special need learners experiencingbarriers in inclusion elementary school. This research purpose was to describe special educator teacher’s role inimplementing the activities of identification, assessment, program arranging, program implementation, and programevaluation. The research method applied was descriptive qualitative approach. The data collection techniques wereobservation, interview, and documentation. The data analysis technique used was data reduction, data display, andconclusion drawing / verification.The research result was special educator teacher doing the activities of identificationand assessment in early learning activity, program arranging in the form of individual learning program, programimplementation and evaluation. This research conclusion was special educator teacher had implemented special needprogram involving the activities of assessment, program arranging, program implementation, and evaluation had runwell.Keywords: Special educator teacher’s role, special need program, inclusion school